Cadmium Exposure-Sedum alfredii Planting Interactions Shape the Bacterial Community in the Hyperaccumulator Plant Rhizosphere - Hou, Dandi (Appl Environ Microbiol, 2018)
Rhizospheric bacteria play important roles in plant tolerance and activation of heavy metals. Understanding the bacterial rhizobiome of hyperaccumulators may contribute to the development of optimized phytoextraction for metal-polluted soils. We used 16S rRNA gene amplicon sequencing to investigate the rhizospheric bacterial communities of the cadmium (Cd) hyperaccumulating ecotype (HE) Sedum alfredii in comparison to its nonhyperaccumulating ecotype (NHE). Both planting of two ecotypes of S. alfredii and elevated Cd levels significantly decreased bacterial alpha-diversity and altered bacterial community structure in soils. The HE rhizosphere harbored a unique bacterial community differing from those in its bulk soil and NHE counterparts. Several key taxa from Actinobacteria, Bacteroidetes, and TM7 were especially abundant in HE rhizospheres under high Cd stress. The actinobacterial genus Streptomyces was responsible for the majority of the divergence of bacterial community composition between the HE rhizosphere and other soil samples. In the HE rhizosphere, the abundance of Streptomyces was 3.31- to 16.45-fold higher than that in other samples under high Cd stress. These results suggested that both the presence of the hyperaccumulator S. alfredii and Cd exposure select for a specialized rhizosphere bacterial community during phytoextraction of Cd-contaminated soils and that key taxa, such as the species affiliated with the genus Streptomyces, may play an important role in metal hyperaccumulation. IMPORTANCE Sedum alfredii is a well-known Cd hyperaccumulator native to China. Its potential for extracting Cd relies not only on its powerful uptake, translocation, and tolerance for Cd but also on processes underground (especially rhizosphere microbes) that facilitate root uptake and tolerance of the metal. In this study, a high-throughput sequencing approach was applied to gain insight into the soil-plant-microbe interactions that may influence Cd accumulation in the hyperaccumulator S. alfredii. Here, we report the investigation of rhizosphere bacterial communities of S. alfredii in phytoremediation of different levels of Cd contamination in soils. Moreover, some key taxa in its rhizosphere identified in the study, such as the species affiliated with genus Streptomyces, may shed new light on the involvement of bacteria in phytoextraction of contaminated soils and provide new materials for phytoremediation optimization.